1990
DOI: 10.1056/nejm199003153221103
|View full text |Cite
|
Sign up to set email alerts
|

Gastrinomas in the Duodenums of Patients with Multiple Endocrine Neoplasia Type 1 and the Zollinger-Ellison Syndrome

Abstract: In patients with multiple endocrine neoplasia type 1 (MEN-1), gastrinomas are common and thought to occur predominantly in the pancreas. We describe eight patients with MEN-1 and hypergastrinemia (seven with the Zollinger-Ellison syndrome) in whom we searched for neuroendocrine tumors in the pancreas and duodenum. Tumors were found in the proximal duodenum in all eight patients: solitary tumors (diameter, 6 to 20 mm) in three patients and multiple microtumors (diameter, 2 to 6 mm) in the other five. Paraduoden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
209
1
6

Year Published

1991
1991
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(225 citation statements)
references
References 20 publications
9
209
1
6
Order By: Relevance
“…The vast majority of tumors are found in this pancreatic head-duodenal area, mainly in the duodenal submucosa (40%-50%), the head of the pancreas (30%-50%) or in the neighboring lymph nodes (19%) [2] . Ectopic gastrinomas are rare (< 5%) and have been reported in the stomach, ovaries, omentum, kidneys, lymph nodes, jejunum, esophagus, extrahepatic biliary tree, and liver [6][7][8][9][10][11][12][13][14][15] . The latter has been reported in fewer than 20 cases [16,17] .…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of tumors are found in this pancreatic head-duodenal area, mainly in the duodenal submucosa (40%-50%), the head of the pancreas (30%-50%) or in the neighboring lymph nodes (19%) [2] . Ectopic gastrinomas are rare (< 5%) and have been reported in the stomach, ovaries, omentum, kidneys, lymph nodes, jejunum, esophagus, extrahepatic biliary tree, and liver [6][7][8][9][10][11][12][13][14][15] . The latter has been reported in fewer than 20 cases [16,17] .…”
Section: Discussionmentioning
confidence: 99%
“…It is now well established from numerous studies that resection of visible pancreatic tumours in these patients rarely (Ͻ2%) leads to cure [3,7,8,66,71,73,77]. In 1990 Pipeleers-Marischal et al [70] reported that all of the gastrinomas in their patients with ZES and MEN-1 were duodenal in location and they suggested that it might be possible to cure these patients if careful duodenal exploration was performed. Subsequently, a prospective NIH study in patients primarily without MEN-1 demonstrated that to detect duodenal gastrinomas it was necessary that a routine duodenotomy had to be performed [22] and also transillumination of the duodenum at surgery [78] was recommended to properly place the duodenotomy incision [22].…”
Section: Specific Aspects Of Treatment Of the Primary Gastrinoma In Pmentioning
confidence: 99%
“…In the past, studies with ultrasound or CT have been largely used but they can miss 30-60% of patients with liver metastases [7,9,68,69]. An additional factor contributing to the confusion of treating patients with ZES and MEN-1 is the recent recognition that these patients usually have duodenal gastrinomas and the pancreatic lesions seen on imaging studies are not usually the gastrinomas [70][71][72]. This has led to uncertainty about what percentage of these patients might be curable because in previous surgical studies concluding cure was very rare in MEN-1 patients with ZES, only detailed explorations of the pancreas and pancreatic resections were performed [3,66,73].…”
Section: Specific Aspects Of Treatment Of the Primary Gastrinoma In Pmentioning
confidence: 99%
“…Patients with sporadic ZES are found to have a solitary duodenal or pancreatic gastrinoma. In the remaining patients, ZES is part of multiple endocrine neoplasia type 1 (MEN1) syndrome (Pipeleers-Marichal et al 1990, Thompson 1998. Size varies with the site of the tumor; pancreatic gastrinomas are often larger than 1 cm, whereas gastrinomas of the duodenum are usually smaller (Donow et al 1991, Sugg et al 1993.…”
mentioning
confidence: 99%